Implementation of Islamic Business Ethics in Enhancing Entrepreneurship: A Case Study of Wisma Barbershop - Andrian Syaputra; Jannah, Nurul; Harianto, Budi (Jurnal Manajemen Bisnis, 2024)
Some common problems include a lack of understanding and inconsistent implementation of Islamic business ethics. Many barbershop owners and employees still struggle to apply these ethics consistently in their daily operations. This issue, coupled with intense competition in the barbershop industry, affects the effective implementation of Islamic business ethics. The aim of this research is to examine how Islamic business practices are applied in an entrepreneurial context, specifically focusing on barbershops. A descriptive qualitative case study method was employed to gain an in-depth understanding of the application of Islamic business ethics in Wisma Barbershop's daily operations and its impact on entrepreneurship. Data for this research were collected through interviews with barbershop owners. For analyzing qualitative data, the Miles and Huberman model was used. The findings indicate that Wisma Barbershop adheres to Islamic business ethics, incorporating principles such as morality and honesty, monotheism, justice, freedom, and responsibility. This study demonstrates that implementing Islamic business ethics in barbershops involves more than just providing services; it reflects a commitment to ethical business practices.